Effects of the Use of Probiotics in Post-Bariatric Surgery Obesity: Meta-Umbrella of Systematic Reviews - Danilo Ferreira de Sousa; Luciane Bresciani Salaroli (Obesities)
Obesity is a multifaceted health issue linked to conditions like type 2 diabetes, hypertension, and cardiovascular disease. Bariatric surgery is a well-established method for significant weight loss and health improvement, but maintaining weight loss and recovering post-surgery can be challenging. Probiotics, beneficial live microorganisms, are suggested as potential aids in managing obesity and its complications, but research on their effectiveness in this context is limited and diverse. This study aimed to evaluate the impact of probiotics on obesity in individuals post-bariatric surgery. A meta-umbrella review was conducted, analyzing systematic reviews and meta-analyses of probiotics’ effects. The review included studies from PubMed, Scopus, EMBASE, and Cochrane Library, focusing on weight loss, body composition, and metabolic parameters. Four systematic reviews met the criteria. The findings indicate that probiotics may significantly reduce waist circumference and body weight, and improve lipid and liver markers. However, their effects on glycemic parameters, quality of life, and adverse events were less clear. Overall, probiotics might offer modest benefits in managing weight and improving certain metabolic parameters after bariatric surgery. However, their overall efficacy, especially regarding glycemic control and quality of life, remains uncertain. Further high-quality research is needed to confirm these findings and elucidate the mechanisms involved.